1986
DOI: 10.1007/bf00752882
|View full text |Cite
|
Sign up to set email alerts
|

Crossvalidation of some psychometric properties of the CSQ and its differential return rate as a function of token financial incentive

Abstract: The Consumer Satisfaction Questionnaire (CSQ) was developed by Larsen, Atkisson, Hargreaves, and Nguyen (1979) and has been mentioned as a possible "standard scale" for the evaluation of consumer satisfaction with mental health treatment because of its unidimensionality, reliability, validity and ease of use. A mail survey of ex-clients who had terminated treatment during the preceding year from one of six offices of a regional mental health center in the Rocky Mountain area strongly cross-validated these char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…After combining the results of both search strategies and removing the duplicates, a total of 105 RCTs were included in the analysis (figure 1). 10 18–115 The inter-rater reliability was found to be good during the screening of articles for both search strategies (kappa statistic of 0.65 and 0.74).…”
Section: Resultsmentioning
confidence: 97%
“…After combining the results of both search strategies and removing the duplicates, a total of 105 RCTs were included in the analysis (figure 1). 10 18–115 The inter-rater reliability was found to be good during the screening of articles for both search strategies (kappa statistic of 0.65 and 0.74).…”
Section: Resultsmentioning
confidence: 97%
“…A total of 22 studies were identified on this topic (Table 25; see p. 164). 157,163,179,182,207,228,232,234,241,244,246,[249][250][251][252][253][254][255][256][257][258][259] All but two were randomised trials; eight were on healthrelated topics. 179,228,246,250,[252][253][254]256 Several involved manipulation of multiple aspects of incentives (e.g.…”
Section: Identified Studiesmentioning
confidence: 99%
“…157,163,179,182,207,228,232,234,241,244,246,[249][250][251][252][253][254][255][256][257][258][259] All but two were randomised trials; eight were on healthrelated topics. 179,228,246,250,[252][253][254]256 Several involved manipulation of multiple aspects of incentives (e.g. magnitude and timing of delivery); the subsections below reflect the principal foci of the identified articles.…”
Section: Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation indicated that it was highly unlikely that a sufficiently large sample of clients from the preceding 5 years could be contacted to provide a reasonable basis for generating conclusions. Subsequent research in the same geographical area (Weltzien, McIntyre, Ernst, Walsh, & Parker, 1985) demonstrated that at least one area mental health center had a similar problem in locating ex-clients for follow-up purposes. The high degree of mobility of woods product workers, a locally important industry, was cited as a probable cause of difficulty in follow-up.…”
Section: Segmentmentioning
confidence: 99%